2000
DOI: 10.1016/s1097-2765(00)80433-5
|View full text |Cite
|
Sign up to set email alerts
|

β-globin Gene Switching and DNase I Sensitivity of the Endogenous β-globin Locus in Mice Do Not Require the Locus Control Region

Abstract: We have generated mice with a targeted deletion of the beta-globin locus control region (LCR). Mice homozygous for the deletion die early in embryogenesis but can be rescued with a YAC containing the human beta-globin locus. After germline passage, deletion of the LCR leads to a severe reduction in expression of all mouse beta-like globin genes, but no alteration in the developmental specificity of expression. Furthermore, a DNase I-sensitive "open" chromatin conformation of the locus is established and mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
183
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 223 publications
(203 citation statements)
references
References 40 publications
18
183
0
2
Order By: Relevance
“…Given this observation and the presence of DNasehypersensitive sites at both of these regions in erythroid cells, these sequences are candidates for erythroid regulatory elements. The results of the LCR deletions (24)(25)(26) suggest that formation of a generalized nuclease-sensitive chromatin structure in erythroid cells is accomplished by sequences other than the LCR, and one or both of these conserved hypersensitive sites may play a role in this process. We cannot at present eliminate the possibility, however, that either or both of these regions also may be involved in regulation of the proximal ORGs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given this observation and the presence of DNasehypersensitive sites at both of these regions in erythroid cells, these sequences are candidates for erythroid regulatory elements. The results of the LCR deletions (24)(25)(26) suggest that formation of a generalized nuclease-sensitive chromatin structure in erythroid cells is accomplished by sequences other than the LCR, and one or both of these conserved hypersensitive sites may play a role in this process. We cannot at present eliminate the possibility, however, that either or both of these regions also may be involved in regulation of the proximal ORGs.…”
Section: Discussionmentioning
confidence: 99%
“…The LCR is a major cis-regulatory sequence in erythroid cells, and so we examined the possibility that it also could play a role in regulation of linked genes in olfactory tissue by comparing ORG expression in olfactory epithelium of wildtype mice and mice homozygous for a deletion of the ␤-globin LCR (26). Using the exon assignments derived from the 5Ј RACE products, we designed PCR primers to amplify cDNAs from spliced mRNA in mouse olfactory epithelium.…”
Section: Org Expression Is Unaffected By Deletion Of the ␤-Globin Lcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of targeted deletions of the endogenous ␤-globin LCR in mice and in cultured cells have revealed that the LCR is not required for initiation or maintenance of general DNase I sensitivity of the locus, hyperacetylation of histones, or low-level transcription, but it is essential for achieving high levels of transcription (Epner et al 1998;Bender et al 2000;Schübeler et al 2001). Given the similar chromatin structure and expression of the ␤-globin loci in uninduced MEL cells and the ⌬LCR cells, we wished to determine if the differentiation-dependent events such as NF-E2 binding, PIC assembly, and elongation were LCR-dependent steps.…”
Section: Allele-specific Chip Analysis For ⌬Lcr/wt Heterozygous Micementioning
confidence: 99%
“…Surprisingly, studies of the targeted deletion of the LCR from the endogenous ␤-globin gene locus (⌬LCR) have revealed that the LCR is not required for the generalized DNaseI sensitive conformation of the locus or chromatin remodeling and histone hyperacetylation of the ␤-globin promoter (Epner et al 1998;Bender et al 2000;Schübeler et al 2001); however, transcription from the ⌬LCR allele is decreased to 1%-4% of wild-type (WT) levels (Bender et al 2000;Schübeler et al 2001). These results suggest that the LCR stimulates transcription at an event downstream of promoter remodeling, although the molecular mechanism of LCR function has not been determined.…”
mentioning
confidence: 99%